Associations between composite systemic inflammation indicators(CAR, CLR, SII, AISI, SIRI, and CALLY) and metabolic dysfunction-associated fatty liver disease (MAFLD): evidence from a two-stage study in China - Zhao, Jing; Zhou, Quan; Wang, Yun; Xie, Fangfei; Fan, Jingyi (Frontiers in Immunology, 2025)
BackgroundThe redefinition from nonalcoholic fatty liver disease (NAFLD) to metabolic dysfunction-associated fatty liver disease (MAFLD) highlights metabolic dysfunction’s central role. While systemic inflammation drives MAFLD, large-scale evidence linking novel composite immune-inflammatory markers to MAFLD remains limited. This study evaluates six such markers and their association with MAFLD risk in a two-stage study in China.MethodsThis two-stage study included a case-control analysis (7,894 MAFLD cases and matched controls) and a prospective cohort study (8,627 participants, median follow-up 2.37 years). Six composite immune inflammation-related markers (CAR, CLR, SII, AISI, SIRI, and CALLY) were derived from routine blood tests. Multivariable logistic and Cox regression models were used to assess associations with MAFLD risk, with adjustment for metabolic confounders. Restricted cubic splines (RCS) explored nonlinear relationships, and receiver operating characteristic (ROC) and decision curve analyses (DCA) evaluated predictive performance and clinical utility. The Cochran's Q test was used to evaluate the heterogeneity between groups to verify the influence of covariates.ResultsAll indicators show a significant nonlinear threshold effect relationship with the risk of MAFLD. CAR, CLR, SII, AISI, and SIRI exhibit a rapid increase in risk initially, followed by a plateau, while CALLY shows the opposite trend. Subgroup analysis indicates that SIRI is more strongly associated with MAFLD in women. Models combining these indicators with metabolic factors demonstrate superior predictive performance (AUC > 0.8) and clinical net benefit.ConclusionSystemic immune-inflammatory indices exhibit nonlinear associations with MAFLD risk, independent of traditional metabolic factors. This reinforces MAFLD as a systemic inflammatory disease and highlights the potential of anti-inflammatory strategies, especially during the early, reversible stage before the risk plateaus.